2009
DOI: 10.1007/s12583-009-0027-y
|View full text |Cite
|
Sign up to set email alerts
|

Dur’ngoi ophiolite in East Kunlun, Northeast Tibetan plateau: Evidence for paleo-Tethyan suture in Northwest China

Abstract: The A'nyemaqen (阿尼玛卿) ophiolite belt along the southern margin of the East Kunlun (昆仑) Mountains marks the suture formed by the closure of paleo-Tethys. The Dur'ngoi ophiolite in the eastern part of this belt consists of meta-peridotite, mafic-ultramafic cumulates, sheeted dikes and basaltic lavas. The meta-peridotites consist of dunite, harzburgite, lherzolite, feldspar-bearing lherzolite and garnet-bearing lherzolite and contain residual spinel with Cr # [100×Cr/(Cr+Al)] ranging from 30 to 57 and Mg # [100×M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 17 publications
1
53
0
Order By: Relevance
“…R2 plot, they plot primarily in the late-orogenic granitoid field. Because the Proto-Tethys closed during the Early Devonian (Bian et al, 2004;Harrowfield and Wilson, 2005;Jiang et al, 1992;Pan et al, 1996;Reid et al, 2005;Roger et al, 2003;Sengör, 1987;Xu et al, 2003;Yang et al, 1996;Yang et al, 2009;Yin and Harrison, 2000), we suggest that during the Anisian, the EKO may still have been affected by the post-collision deformation between the South Kunlun belt and Middle Kunlun belt, which formed late-orogenic granitoids such as the Balugou granite dike.…”
Section: Petrogenesis Of Granite and Diorite Dikesmentioning
confidence: 77%
See 1 more Smart Citation
“…R2 plot, they plot primarily in the late-orogenic granitoid field. Because the Proto-Tethys closed during the Early Devonian (Bian et al, 2004;Harrowfield and Wilson, 2005;Jiang et al, 1992;Pan et al, 1996;Reid et al, 2005;Roger et al, 2003;Sengör, 1987;Xu et al, 2003;Yang et al, 1996;Yang et al, 2009;Yin and Harrison, 2000), we suggest that during the Anisian, the EKO may still have been affected by the post-collision deformation between the South Kunlun belt and Middle Kunlun belt, which formed late-orogenic granitoids such as the Balugou granite dike.…”
Section: Petrogenesis Of Granite and Diorite Dikesmentioning
confidence: 77%
“…Previous work has revealed that the EKO has undergone at least two stages of orogeny that are closely related to the consumption of the Proto-Tethys (Neoproterozoic to Early Devonian) and Paleo-Tethys (Carboniferous to Late Triassic) oceans (Bian et al, 2004;Harrowfield and Wilson, 2005;Jiang et al, 1992;Pan et al, 1996;Reid et al, 2005;Roger et al, 2003;Sengör, 1987;Xu et al, 2003;Yang et al, 1996;Yang et al, 2009;Yin and Harrison, 2000). The collision between the EKO and the BH-SG is thought to have been a soft collision, which accounts for the lack of significant crustal thickening in the East Kunlun (Yin and Zhang, 1997).…”
Section: Geological Settingmentioning
confidence: 99%
“…It is interesting that the composition of most lavas from these ophiolites is characterized by MORBs and minor OIBs in composition and a distinct lack of IATs and BONs, which is inconsistent with most ophiolites (Robinson and Zhou, 2008;Zhang et al, 2008b). The generation and tectonic nature of these ophiolites are poorly understood, and previous studies have proposed diverse models for determining these factors, including oceanic spreading, back-arc spreading and mantle plume activity (Bian et al, 2004;Guo et al, 2007;Jian et al, 2009a;Yan et al, 2005;Yang et al, 2009;Zhang et al, 2008b). A lack of knowledge of the petrogenesis, mantle sources and geodynamic setting of mafic-ultramafic rocks from these ophiolites is the main reason for such uncertainty and controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean during the Late Permian to Early Triassic (Guo et al, 2007;Yang et al, 2009), with the formation of a large-scale granitoid belt (Fig. 1b;Huang et al, 2014;Xiong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on the Paleo-Tethyan ophiolites in the A'nyemaqen suture zone have been carried out (Fig. 2a), with the conclusion of the Paleo-Tethyan ocean opened as early as Carboniferous (Chen et al, 2001;Bian et al, 2004;Yang et al, 2009). However, recent studies have shown that large amounts of Cambrian ophiolite fragments are also present in the A'nyemaqen suture zone (Fig.…”
Section: Introductionmentioning
confidence: 99%